Vertebral Fractures After Denosumab Discontinuation in Breast Cancer Survivors: A Single Institution Experience. Issue 2 (July 2021) - Yeung, Michele; Ho, Kaylee; Fornier, Monica N.; Farooki, Azeez
Background: Denosumab is approved to prevent fragility fractures in patients with osteoporosis at high risk for fracture and to prevent bone loss in patients with breast and prostate cancer who receive endocrine therapy. The antiresorptive effect of denosumab rapidly dissipates when it is delayed or discontinued, but the risk for, and incidence of, multiple clinical vertebral fractures in patients with breast cancer after stopping denosumab is currently unclear. Question/Purposes : We sought to identify the incidence of clinical vertebral fractures in patients with breast cancer who received at least 2 doses of denosumab (60 mg) and then discontinued the medication. Methods : We conducted a retrospective chart review to identify patients with a history of breast cancer who were treated with denosumab between June 1, 2010, and July 18, 2018, at Memorial Sloan Kettering Cancer Center. We identified 335 postmenopausal women and 1 man with nonmetastatic breast cancer who received their final denosumab injection at least 6.5 months earlier. Data recorded included baseline bone density and the incidence of vertebral fractures after denosumab discontinuation. Results : The median age of patients was 62 years. Patients received between 2 and 13 denosumab doses before drug discontinuation. Most of the patients (310; 92.3%) were also treated with aromatase inhibitors. Of the 194 patients with baseline bone density data, 50 (25.8%) had normal bone density, 97 (50.0%) had osteopenia, and 47 (24.2%) had osteoporosis. The median follow-up duration from the last denosumab dose was 18.5 months. We identified 1 case of spontaneous vertebral fractures after denosumab stoppage. We found no cases of osteonecrosis of the jaw or atypical femur fracture. Most of the patients (88%) had a gap in denosumab dosing. Conclusions : Clinicians treating patients with breast cancer—especially those continuing to take aromatase inhibitors—should be aware of the possible risks of delaying doses of or discontinuing denosumab and should educate their patients accordingly. Prospective studies are needed to fully evaluate the risks of stopping or delaying denosumab.